Efecto de la ferEffect of phosphate fertilizer on the soil cadmium content in four types of Chilean soils - Bonomelli, Claudia; Bonilla, Carlos; Valenzuela, Adriana (Pesquisa Agropecuaria Brasileira, 2003)
Phosphate fertilizers may contain cadmiun (Cd) which may become part of the trophic chains. The objective of this study was to evaluate the effect of phosphate fertilizer on available Cd content in four Chilean soil types, belonging to orders Alfisol, Inceptisol, Ultisol and Andisol. Treatments consisted of control without P fertilizer and P application with commercial triple superphosphate containing 53.2 mg Cd per kg of fertilizer. The dose of phosphate fertilizer applied was enough to reach the level of 30 mg kg-1 P-Olsen. The soils were incubated up to 90 days, at 25oC and field capacity. The experimental design was completely randomized with three replications, and the experimental unit was a container with 250 g of soil (dry matter). Available Cd was measured at 1, 2, 7, 14, 21, 36, 49, 63, 77, and 90 days after incubation. Application of P at agronomic rate using fertilizer with a high Cd content produced significant effects on available Cd content in the soil types studied, however, incubation time period did not present such effect.
Keywords: heavy metals; soil sorption; contamination; trophic levels